SINTESIS DAN UJI AKTIVITAS ANTIMALARIA SENYAWA (1)-N-BENZIL-1,10- FENANTROLINIUM BROMIDA - Ruslin Hadanu; Sabirin Mastjeh; Jumina Jumina; Mustafa Mustafa; Eti Nurwening Sholikhah; Mahardika Agus Wijayanti (Molluca Journal of Chemistry Education (MJoCE), 2011)
A synthetic methods was employed to prepare (1)-N-benzyl)-1,10-phenanthroliniumbromide 4 from 1,10phenanthroline 3 and benzylchloride 1 through substitution and alkylation reactions. The compound (1)-Nbenzyl)-1,10-phenanthroliniumbromide 4 was tested through antiplasmodial test. The benzylbromide 2 was synthesized through substitution reaction of benzylchloride 1 and NaBr which has a yield of 74.25%. The (1)-N-benzyl)-1,10-phenanthroliniumbromide 4 was synthesized from 1,10-phenanthroline 3 using benzylbromide 2 reagents which refluxed for 8 hours with 84.04% yields. The results of testing in in vitro antiplasmodial activity at chloroquine-resistant Plasmodium falciparum FCR3 strain to (1)-N-benzyl)-1,10- phenanthroliniumbromide 4 has high antimalarial activity (IC50 : 0.10Â±0.04 ÂµM)